Factors associated with chlamydia trachomatis infection in women resident in the state of Roraima, Brazil - Sequeira, Bianca Jorge; Loureiro, Edvaldo Carlos Brito; Costa, Wagner do Carmo (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: Chlamydia trachomatis is an obligate intracellular bacterium. The genital infection caused by this bacterium is considered the most common sexually transmitted bacterial disease in the world. However, despite the magnitude of the problem, the state of Roraima does not address studies that establish its prevalence in the female population. Objective: To determine the prevalence of genital C. trachomatis in women living in Roraima and to evaluate the correlation of results with sexual behavior. Methods: A descriptive, cross-sectional and quantitative study involved 273 sexually active women, aged 18–60, resident in Roraima. In the beginning, 273 endocervical samples were collected through speculum examination in order to carry out the direct immunofluorescence test for C. trachomatis. In addition to laboratory tests for the detection of C. trachomatis, a survey was conducted through a clinicalepidemiological questionnaire, which determined the sociocultural and sexual profile of each participant. Results: The prevalence of C. trachomatis infection was determined in 33.73%. Association between C. trachomatis infection and women who have a family income greater than five minimum wages was also observed. Besides, chlamydial infection was connected with pain and bleeding during intercourse. The link between C. trachomatis infection and anal sex was demonstrated as well. Having a partner who works or had worked in mining and more than one sexual partner was pointed as a risk factor. Conclusion: The results indicate the high prevalence of C. trachomatis infection among the studied population, and factors such as practice of anal sex and having as a sexual partner someone who works or had worked in mining were pointed as associated with the infection.